The profile of the electric field on the earth discontinuity with a lightning conductor - Ali Khechekhouche (International Journal of Energetica)
In this paper, we present some results of investigations carried out in the electric field distribution of both horizontal and vertical lightning conductors in the case of discontinuous earth. The conductors may be situated as well as in the upper or the lower earth part. The electric field distribution was determined in the case of lightning conductor situated between the high voltage rod and the discontinuity (interface) and also in the case of high voltage rod situated between the lightning conductor and the discontinuity. In some situations the electric field distribution on the plan are smaller than defined by the electro-geometrical model. We attribute this result to the great field intensity at the discontinuity, which reduce the lightning conductor discharge capture effect. This is in concordance with the results concerning the electrical strength of such air gaps without lightning conductors.